Comparison of NaCl Levels in Seasoning Powder Formulation of Nagara Bean Flour (Vigna unguiculata Ssp. cylindrica) and Oyster Mushroom Using the Mohr Method by Direct Titration and Ash Mineral Titration - Susi Susi; Hisyam Musthafa Al Hakim (Journal of Applied Food Technology, 2022)
The use of excessive salt in the food product poses a potential health problem. For this reason, efforts should be made to reduce salt consumption. One of food products containing a significant amount of salt is flavor enhancer. The method of measuring salt content is crucial in seasoning powder to provide a good description of the salt content. Salt content measurement in foodstuffs was analyzed by the Mohr method that can be carried out by direct titration or by kiln to obtain mineral ash. The direct titration method will give faster results than the mineral ash titration. This research aims to obtain a comparison of salt content through direct titration and mineral ash titration, the deviation, and correlation between two methods. The results of the NaCl measurement content with the direct and the ash mineral titration method were significantly different, the correlation regression of the direct titration followed the equation Y = 15.368 + 1.021X. The direct titration showed higher measurement results than the ash mineral titration method. Mohr's method by ash titration is more precise and reliable for measuring NaCl in seasoning powder but requires a longer time.